Interplay and multiscale modeling of complex biological systems - Carlo Bianca (AIMS Biophysics, 2022)
Recently the understanding of complex biological systems has been increased considering the important interplay among different scholars coming from different applied sciences such as mathematics, physics and information sciences. As known, the modeling of a complex system requires the analysis of the different interactions occurring among the different components of the system. Moreover, the analysis of a complex system can be performed at different scales; usually the microscopic, the mesoscopic and the macroscopic scales are the most representation scales. However, a multiscale approach is required. A unified approach that takes into account the different phenomena occurring at each observation scale is the desire of this century. This editorial article deals with the topic of this special issue, which is devoted to the new developments in the multiscale modeling of complex biological systems with special attention to the interplay between different scholars.